The Changing Role of Criminal Law in Controlling Corporate Behavior - Anderson, James M. (RAND Corporation, 2014)
This report addresses the use of criminal sanctions to control corporate behavior-prosecutions both of corporations and of employees for actions taken on corporations' behalf. The authors describe the current state of the use of criminal sanctions in controlling corporate behavior, describe how the current regime developed, and offer suggestions about how the use of criminal sanctions to control corporate behavior might be improved.